RIGHT OF UNTRIED PRISONERS STUDY OF CASES WHEN UNTRIED PRISONERS WERE TAKEN TO COURT - Boonrak, Tisirak; Vorapatr, Thanee (Journal of MCU Nakhondhat, 2023)
This research article aims to study of the rights of untried prisoners when untried prisoners go to court. By studying concepts, theories, principles of law, and practical guidelines for protecting the rights and liberties of untried prisoners when untried prisoners were taken to court in Thailand and abroad to propose guidelines for development, amendments, and improvements in relevant laws. By using the documentary research method as the main method. By studying from the provisions of laws, rules, regulations, books, textbooks, academic articles, legal journals, theses, electronic data. Various relevant research papers, both in Thailand and abroad. The study found that the present, the practice and legal principles provided in the constitution are inconsistent. The rights of untried prisoners are violated during trial. The study found that, at present, the practice and legal principles provided in the constitution are inconsistent and the rights of untried prisoners are violated untried prisoners; In which the inmates pending trial are still considered innocent until the court delivers a final verdict indicating that such person has committed an offence. Therefore, such problems must be resolved in order to comply with international legal principles. Therefore, it should be amended as follows: 1) There should be a provision clearly stipulating that inmates during consideration can wear their own clothes, except in cases where it is necessary to wear a prison uniform that is completely different from that of a prisoner. Especially if it is the case where the court orders the withdrawal of untried prisoners to the court for proceedings, they must be allowed to wear internationalist attire. 2) The use of restraints on untried prisoners should be avoided while transporting pending prisoners to court. 3) The detention of untried prisoners during court proceedings should be concealed from the public eye. 4) The provisions on such matters should be added to the Prisons Act B.E. 2560